Improving the accuracy of prediction using singular spectrum analysis by incorporating internet activity - Badenhorst, Dirk Jakobus Pretorius (Stellenbosch : Stellenbosch University, 2013)
Thesis (MComm)--Stellenbosch University, 2013.